Pengaruh Handling Complaint Dalam Meningkatkan Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Kasus Pada Wahas Catering) - Wardhana, Nurani Lembut Putri; Arifin, Rois; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract Increasing competition in the culinary service industry demands that companies improve service quality to create customer satisfaction and loyalty. This study aims to analyze the effect of complaint handling on customer loyalty, with customer satisfaction as an intervening variable at Wahas Catering. This study used a quantitative approach with path analysis techniques to determine the direct and indirect relationships between variables. The study sample consisted of 75 respondents, who were Wahas Catering customers who had filed complaints and made repeat purchases. The results showed that complaint handling had a positive and significant effect on customer satisfaction with a significance value of 0.017. Furthermore, complaint handling also had a significant effect on customer loyalty with a significance value of 0.021. Customer satisfaction was proven to have a significant effect on customer loyalty with a significance value of 0.000. The Sobel test showed that customer satisfaction significantly mediated the relationship between complaint handling and customer loyalty. These findings emphasize the importance of complaint handling as a primary strategy in improving the customer experience, which ultimately drives loyalty to the catering service. This study provides implications for Wahas Catering management to strengthen its complaint handling system as a strategic effort to create satisfied and loyal customers on an ongoing basis. Keywords: Handling Complaints, Customer Satisfaction, Customer Loyalty, Path Analysis, Wahas Catering